Liolaemus ditadai - Pelegrin, Nicolas (2017)
This species is listed as Data Deficient because it is known only from a few specimens, and there are nodata on population size and trends and the extent to which apparent threats may affect it. However, theonly known population is restricted to a small area and more research is needed to better determine itspopulation status and threats